STUDENTS LEARNING CULTURE IN HIGHER EDUCATION AFTER THE COVID-19 PANDEMIC - Muthahharah Thahir; Andre Julius; Badrud Tamam; Wahyuni Thahir (Conciencia, 2023)
This study aims to analyze the description of student learning culture in higher education after the Covid-19 pandemic so that it can develop better learning productivity. The type of research used is quantitative descriptive research using a case study method conducted at Ma'some University with a total research population of 150 students at the Faculty of Teacher Training and Education. The results showed that students in higher education classified the learning culture implemented through social interactions and the value system in the substance of learning culture as high after the Covid-19 pandemic with a score of 3.32 and 3.34 for each dimension. Students in higher education can adapt to post-Covid-19 pandemic learning. However, universities still need to improve and maintain the stability of student learning culture by being conducive to social interactions and values and systems in the substance of learning culture.